Initial clinical trial of a novel hemostat, TDM‐621, in the endoscopic treatments of the gastric tumors. (December 2014) - Yoshida, Masashi; Goto, Naoki; Kawaguchi, Minoru; Koyama, Hidehiko; Kuroda, Junko; Kitahora, Tetsuji; Iwasaki, Hiroyuki; Suzuki, Shinji; Kataoka, Mikinori; Takashi, Fujii; Kitajima, Masaki
Abstract: Background and Aim: The feasibility of TDM‐621, the synthetic infectious agent‐free peptides, was tested in hemostasis of the bleeding after endoscopic treatments of the gastric tumors. Methods: The patients who underwent endoscopic mucosal resection (EMR) or endoscopic submucosal dissection (ESD) were enrolled in the present study. The subject of hemostasis was the oozing after the EMR or ESD. The hemostatic effect, the secondary hemorrhage from one postoperative day to the day before discharge and operability were studied. Results: The hemostatic effects were assessed in 12 patients. It was "remarkably effective" in 11 patients and "effective" in 1 patient. The operability was "very easy" in two patients, "easy" in eight patients and "acceptable" in two patients. No secondary hemorrhage was observed in all of 12 patients. No adverse effect considered to be related to TDM‐621 was observed. Conclusion: It was shown that hemostasis using TDM‐621 was feasible after endoscopic treatments of the gastric tumors without any technical trouble or adverse event.